Persaingan Antariksa antara Amerika Serikat dan Rusia di Abad ke-21: Fase Baru Astropolitika - Henry, Yonaso; Ghiffary, Muhammad Kamil (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
Since the launch of Sputnik 1 in 1957, the United States and the Soviet Union have engaged in intense competition in space exploration. Although the rivalry formally ended in 1975 with the U.S. emerging as the victor, in the 21st century the space competition between the United States and Russia has taken on a more dynamic character compared to the singularly competitive nature of the Cold War era. This research aims to identify the emerging themes in U.S. space policy by applying an institutionalist perspective, focusing on the case study of the Joe Biden administration (2021–2025). The findings indicate that U.S. space policy reflects a shift in characteristics, including a transition from unilateral exploration toward joint governance, as well as cooperation and alliances within global space politics—whether under the framework of international organizations or otherwise. This argument is supported by evidence of changing U.S. policies in viewing outer space as a political instrument across different presidential administrations. It can therefore be concluded that the United States has undergone a transformation in how it treats and utilizes outer space as an instrument of foreign policy—one now dominated by cooperation aimed at shaping space governance in line with both its domestic and international interests. Hence, strengthening global governance mechanisms is essential to manage space competition and maintain international stability.